In House Training: Improvement to Teacher Skills in the Implementation of Problem Based Learning - Rakhmawati, Dewi; Kawuryan, Sekar Purbarini; Adi, Banu Setyo (Jurnal Prima Edukasia, 2024)
The purpose of this research is to improve the ability of teachers to apply the Problem Based Learning Model through IHT at Vidya Qasana Public Elementary School.  The method and design of this research is action research carried out with research procedures based on the Kemmis and Taggart principles which include the following activities: (1) planning, (2) implementation of action, 3) observation, (4) reflection or evaluation.  Increasing the ability of teachers to apply the PBL Learning Model through the application of IHT has increased. The increase occurred due to time management activities in the form of synchronization of iHT implementation time and the mentoring process from classical to group. This has an impact on teacher participation in participating in IHT activities. In cycle 1, the number of teachers who obtained the very good category in the aspect of teacher participation in IHT activities was 62.5% and increased to 87.5% in cycle 2. In the aspect of school principals carrying out IHT activities, cycle 1 achievement of 25% then increased to 100% in the cycle The ability of teachers to apply the Problem Based Learning Model has increased. The increase was after there was an increase in teacher participation in following IHT, thus impacting teachers' understanding and ability to apply PBL in learning. This can be seen from the percentage of teachers who obtained the very good category. In cycle 1, the number of teachers who obtained the very good category in the aspect of lesson plan PBL development was 62.5% and increased to 87.5% in cycle 2. In the aspect of implementing PBL in learning, cycle 1 achievement of 25% then increased to 87.5% in cycle 2